Tudor textiles - Lynn, Eleri ca. 20. Jh (Yale University Press in association with Historic Royal Palaces, 2020)
At the Tudor Court, textiles were ubiquitous in decor and ceremony. Tapestries, embroideries, carpets, and hangings were more highly esteemed than paintings and other forms of decorative art. Indeed, in 16th-century Europe, fine textiles were so costly that they were out of reach for average citizens, and even for many nobles. 0This spectacularly illustrated book tells the story of textiles during the long Tudor century, from the ascendance of Henry VII in 1485 to the death of his granddaughter Elizabeth I in 1603. It places elaborate tapestries, imported carpets, lavish embroidery, and more within the context of religious and political upheavals of the Tudor court, as well as the expanding world of global trade, including previously unstudied encounters between the New World and the Elizabethan court. Special attention is paid to the Field of the Cloth of Gold, a magnificent two-week festival-and unsurpassed display of golden textiles-held in 1520. Even half a millennium later, such extraordinary works remain Tudor society's strongest projection of wealth, taste, and ultimately power